Use of texture fading in the treatment of food selectivity. - Shore, B A (1998)
Children with feeding disorders often display severe food selectivity. For many of these children, consuming highly textured foods may be aversive or potentially dangerous because of frequent gagging. The purpose of this study was to demonstrate the efficacy of texture fading in the treatment of food selectivity displayed by 4 children. Treatment involved the gradual addition of higher textures based on the results of periodic probes. In addition, food acceptance and swallowing were reinforced, while food refusal and food expulsion were placed on extinction. Results showed that all participants successfully advanced to consumption of age-appropriate texture and volume. The results suggest that texture fading with intermittent probes at higher textures may be an effective method for the treatment of food selectivity by texture.